Design of SCADA based solar power plant for clean water irrigation system in remote areas - Mu’ammar, Rais; Nugroho, Prapto; Multa Putranto, Lesnanto (International Journal of Engineering and Technology, 2018)
The study aimed to design a supervisory control and data acquisition (SCADA) system to control solar power plants for clean water irrigation system during the dry season in remote areas. The SCADA system contrived is expected to be able to meet the main elements of the SCADA architecture. Accordingly, following steps were conducted, starting from designing the human machine interface (HMI) in the master station (MS), mapping out the microcontroller as a remote terminal unit (RTU) and designing the communication path between MS and RTU. Furthermore, the SCADA system was tested by the system test to evaluate the SCADA system that was designed meet minimum standard and running well. After tested, the result showed that the system is successfully designed to meet the main elements of SCADA architecture. The system is also able to monitor and control remotely, resulting in more efficient control of user work as well as rapid decision making in order to minimize damage potential when an interruption occurs. For both control and monitor, the MS and RTU in the SCADA system wirelessly communicate.Â Â